Institutional influence on syndicate structure and cross‐border leveraged buyouts. Issue 1 (8th June 2020) - Liu, Chen; Purda, Lynnette; Zhu, Hui
Abstract: We explore the extent to which differences in countries' formal and informal institutions reduce cross‐border leveraged buyout transactions and the potential influence these same institutions have on how private equity (PE) investors choose to enter these transactions. Although institutional differences have frequently been viewed as barriers to cross‐border investment, we find evidence that these same differences may motivate a PE firm's decision to enter the transaction with a syndicate of firms rather than undertaking the transaction on their own. Cultural differences between a PE firm and the target nation are significantly related to the choice to enter the deal via a multinational syndicate. The varying nationalities within the syndicate contribute to enhanced familiarity, with average institutional distances between the syndicate and target firms being significantly lower than for single‐PE‐led deals. Overall, deals undertaken by syndicates are more likely to be successfully completed and require less time in negotiation. These results persist even after accounting for selection bias with regard to target country choice. We explore whether other features of the syndicate are responsible for improved deal outcomes, such as repeated transactions with the same partners, but find no evidence that this is the case.